Supporting Students in Assembler-Level Programming of Processors for Embedded Applications - Grout, Ian; da Silva, Alexandre César Rodrigues [UNESP] (Springer Nature, 2023)
In this paper, the role of different laboratory scenarios (local and remote) are considered for the teaching and learning of processor-based embedded systems. Specifically, the development of teaching and learning approaches to microcontroller programming using assembly code (assembler-level) programming techniques, along with C with embedded assembly code, will be presented and discussed. For the student demographics considered (academic level, motivation, and personal circumstances that may include limited ability to obtain physical hardware), different means to access the core content and laboratory resources for practical work are identified and elaborated with the student requirements and accessibility as a focus. The target hardware is the ubiquitous Arduino UNO platform since due to its available online support, low-cost, robustness, and availability. For at-presence teaching and learning, both the Arduino Integrated Development Environment (IDE) and the Microchip Studio environments are utilized as two means for students to access and program the microcontroller hardware. For remote teaching and learning, a simple web page based on HTML, PHP, JavaScript has been prototyped and will be presented.
Keywords: accessibility; assembly code; Programming